1992
DOI: 10.1007/bf01961245
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of 7,12-dimethylbenz(a)anthracene-induced rat mammary tumors by controlled-release low-dose medroxyprogesterone acetate

Abstract: Since our previous findings had indicated that the androgenic steroid medroxyprogesterone acetate (MPA) exerts potent inhibitory effects on 7,12-dimethylbenz(a)anthracene (DMBA)-induced tumor growth, we have studied the effect of low doses of MPA released from Depo-Provera and from 50:50 poly[DL-lactide-co-glycolide] microspheres in the same DMBA-induced tumor model. The present data show that single subcutaneous injection of a 4-month controlled-release formulation of biodegradable 50:50 poly[DL-lactide-co-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It should be mentioned that in vivo studies have demonstrated that controlled release of low-dose MPA, a compound having androgenic activity, also exerts a potent inhibitory effect on the development and growth of DMBA-induced mammary carcinoma in the rat (243,244). MPA has in fact been clearly shown to exert androgenic inhibitory effects on the growth of human breast cancer cells in vitro (209, 231, (246,247).…”
Section: B Preclinical Datamentioning
confidence: 97%
“…It should be mentioned that in vivo studies have demonstrated that controlled release of low-dose MPA, a compound having androgenic activity, also exerts a potent inhibitory effect on the development and growth of DMBA-induced mammary carcinoma in the rat (243,244). MPA has in fact been clearly shown to exert androgenic inhibitory effects on the growth of human breast cancer cells in vitro (209, 231, (246,247).…”
Section: B Preclinical Datamentioning
confidence: 97%
“…Long-term in vivo studies of progesterone effects in tumor models are sparse. Progesterone treatment inhibits proliferation of established rat mammary tumors (19,20) and PR-transfected MDA-231 (ERÀPRÀ) human breast cancer cells grown into tumors in severe combined immunodeficient mice (21). On the other hand, Michna et al (22) report inhibitory effects of antiprogestins, in which case progesterone would be growth stimulatory.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, MPA has been shown to exert a direct inhibition of the proliferation of ZR-75-1 human breast cancer cells in vitro (Poulin et al, 1989a). An androgen receptor-mediated direct anti-proliferation mechanism (Labrie et al, 1993;Li et al, 1992) as well as an inhibition of the intracellular formation of the active estrogen estradiol by inhibiting 17␤-hydroxysteroid dehydrogenase (17␤-HSD) have been suggested to explain the anti-tumoral effect of MPA in DMBA-induced rat mammary carcinoma (Li et al, 1995).…”
Section: Discussionmentioning
confidence: 99%